Credibility of political marketing on social networking sites in Malaysia: youth perspectives / Azwan Ahzran Perman - Perman, Azwan Ahzran (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
Youths are susceptible to external stimuli, and in the era of the internet, they are on its frontline. Youths are shown to be very close to social networking sites (SNS). In years past, through political marketing and propaganda, the idea of fake news and misinformation is widely debated by all sides on the internet. This paper explores the credibility of political marketing and propaganda via SNS in Malaysia through youth's perceptions. In this qualitative study, seven semi-structured interviews were used to assess youth's perceptions on the credibility of Political Marketing and propaganda on SNS. Through content analysis of the transcriptions, the study found that the participants were aware of fake news and were eager to question and verify political marketing and propaganda information they obtained from SNS. This study highlights the need for a common definition of SNS and the role of political parties and the government to use SNS ethically. Studies on a similar subject need to be expanded to cover greater youth representation across the country.